THE EFFECTS OF COGNITIVELY GUIDED INSTRUCTION ACTIVITIES ON NUMBER SENSE OF MATHAYOMSUKSA 1 STUDENTS - Chorsuwan, Kittitat; Cheausuwantavee, Chommanad; Yamrung, Rungtiwa (Journal of MCU Nakhondhat, 2023)
The purposes of this study are as follows: (1) to compare students’ number sense before and after administrating cognitively guided instruction activities; (2) to compare students’ number sense after administrating cognitively guided instruction activities with the criterion of 70%. The sample of this study included 32 of eighth grade students studying in the second semester of 2022 academic year. They were selected using the cluster random sampling technique. The duration of the research was 14 periods and 45minutes per class. The instruments used in this study were lesson plans and number sense test; objective test there was an index of item – objective congruence (IOC) of 0.67 – 1.00, difficulty (p) of 0.32 – 0.78, discrimination (r) of 0.21 – 0.82 and a reliability of 0.88 and subjective test there was an index of item – objective congruence (IOC) of 0.67 – 1.00, difficulty (P) of 0.22 – 0.50, discrimination (D) of 0.44 – 1.00 and a reliability of 0.90. This research used the One- Group Pretest-Posttest Design. The statistical procedures used for data analysis were a t-test for dependent samples and a t-test for one sample. The results revealed the following: (1) the number sense of the students after experiencing cognitively guided instruction activities were higher than before experiencing the treatment statistically significant at a level of .05; and (2) the number sense of the students after experiencing cognitively guided instruction activities were higher than the criterion of 70%, with a statistically significant level of .05 and an average of 37.38, a standard deviation of 5.79 and amounting to 74.76%.